Making emergency medicine accessible for all: The what, why, and how of providing accommodations for learners and physicians with disabilities. Issue 1 (23rd June 2022) - Poffenberger, Cori McClure; Coates, Wendy C.; Backster, Anika; Rotoli, Jason
Abstract: Individuals with disabilities comprise a substantial portion of the U.S. population but make up only a small subset of medical students and health care providers. Both the Association of American Medical Colleges and the Accreditation Council for Graduate Medical Education have called for increased diversity in the physician workforce, to more closely represent the U.S. patient population and provide culturally effective care. Yet the barriers to disclosure and inclusion for individuals with disabilities in health care are significant, including attitudinal barriers such as stigma and bias, organizational barriers in policies and procedures, and environmental barriers such as resources and physical space. Lack of experience providing accommodations and a lack of knowledge of both what is legally required and what is possible also prevent programs from creating access. Realizing inclusion for individuals with disabilities in a diverse workforce requires emergency medicine programs to be proactive and deliberate in their approach to recruiting, accommodating, and retaining students, residents, and faculty with disabilities. Such efforts are likely to provide benefits that extend beyond those who receive the accommodations.